2010
DOI: 10.1007/s11274-010-0622-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, phenotypic and nutritional characteristics of estuarine soil actinomycetes having broad-spectrum antimicrobial activity derived from an ecologically guided bioprospecting programme

Abstract: No investigation has been done to identify ecological factors selecting for broad-spectrum antimicrobial activity of actinomycetes in the estuaries. Previously, we established that, in the Sundarbans (the world's largest tidal mangrove forest), high antagonistic potential (AP) sampling sites were influenced by tides, while the low AP sites were not. We now report molecular phylogenetic analysis, morphological, physiological and biochemical characteristics of actinomycetes of high AP sites. The effects of soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Mitra et al (2008) [198] believed that antibacterial compound is required to aid in colonizing a newly formed top soil during the transition periods between high and low tides, thereby the periodic oscillations of dry and wet conditions trigger more antagonistic activity of Actinobacteria. In agreement with observations of Mitra et al (2011) [197] , several marine sediment derived Streptomyces strains exhibiting broad antibacterial spectrum and surfactants producing ability were isolated from area constantly affected by tidal gradient in Minnie Bay, A & N islands, India [199] . Furthermore, the high nutrient availability and osmotic flux in the sampling site could be another reason for the broad-spectrum activities exhibited by these strains.…”
Section: Marine Sedimentssupporting
confidence: 90%
See 1 more Smart Citation
“…Mitra et al (2008) [198] believed that antibacterial compound is required to aid in colonizing a newly formed top soil during the transition periods between high and low tides, thereby the periodic oscillations of dry and wet conditions trigger more antagonistic activity of Actinobacteria. In agreement with observations of Mitra et al (2011) [197] , several marine sediment derived Streptomyces strains exhibiting broad antibacterial spectrum and surfactants producing ability were isolated from area constantly affected by tidal gradient in Minnie Bay, A & N islands, India [199] . Furthermore, the high nutrient availability and osmotic flux in the sampling site could be another reason for the broad-spectrum activities exhibited by these strains.…”
Section: Marine Sedimentssupporting
confidence: 90%
“…Streptomyces species found in virgin soil is expected to pro-duce broad-spectrum antimicrobial compounds, hence rendering them to be successful in outcompeting others and effectively colonize the newly formed soil. Mitra et al (2011) [197] suggested that the specific area favorable for obtaining maximum number of isolates with broadspectrum activity in an estuarine setting is limited to the narrow band between the mean high and low tide marks. In brief, the samples collected from sites influenced by tides were suggested to exhibit a high antagonistic potential [198] .…”
Section: Marine Sedimentsmentioning
confidence: 99%
“…The taxonomic data acquired in this study show that selective isolation, dereplication and initial characterization of representative isolates from diverse extreme biomes is a simple and practical way of selecting putatively novel and rare filamentous actinomycetes for exploitative biotechnology. In addition, these data underpin the rational of ecologically guided bioprospecting campaigns featuring actinomycetes (Mitra et al, 2011;Nalini and Prakash, 2017;Liu et al, 2021;Wang et al, 2022). Many of the isolates found to belong to rare and putatively novel taxa were from the litter and mineral horizons of the pine forest indicating that acidophilic and acidotolerant filamentous actinomycetes should feature more prominently in the search for novel bioactive compounds, especially given evidence that such strains are a source of novel antibiotics and acid-stable enzymes (Golińska et al, 2023).…”
Section: Colour-group Assignment Dereplication Of Isolates and Phylogenymentioning
confidence: 99%